LISTENING TO VOICES OF CUSTOMERS FOR INTERNAL QUALITY ASSURANCE DEVELOPMENT IN FUTURE BASIC EDUCATION: PRINCIPLES, CONCEPTS, AND PRACTICES - Bocskull, Visut; Sungtong, Ekkarin (Journal of MCU Nakhondhat, 2023)
This academic article aims to present a framework for customer listening to improve the quality assurance system within basic education institutions in the future. The study integrates principles and concepts of customer Listening from the Malcolm Baldrige Award criteria and the internal quality assurance procedures outlined in the Ministry of Education’s regulations in 2018. These criteria serve as crucial benchmarks for developing the educational institution’s quality management system. The suggested approach includes the following key steps 1) Customer Needs Analysis: Identify and standardize the educational requirements, main goals of the curriculum, management and services, teacher’s instructional management, and child quality development based on the spoken words of customers, parents, and stakeholders. 2) Hierarchical Structure: Implement a hierarchical structure by categorizing and prioritizing customer, parent, and stakeholder requirements according to their significance. Develop a strategic plan based on these strategic needs. 3) Prioritization: Consider the prioritization of each group’s needs and requirements, recognizing that priorities may differ among customers, parents, and stakeholders. 4) Customer Perceptions of Performance: Evaluate the efficiency of customer perceptions of educational performance within the institution. This includes assessing the outcomes, tracking operational performance, and determining whether the institution meets established standards and objectives. This information is crucial for self-assessment reports, strategic marketing decisions, and continuous quality development of the institution. By adapting customer feedback, the author believes it can pave the way for a novel approach to internal quality development within Thai educational institutions, steering them towards excellence in the future.